"Right to the city" (H. Lefebvre, D. Garvey): history and modernity - G. P. Podolian; O. D. Rykhlytska (Ukrainian Cultural Studies, 2021)
The article is devoted to the analysis of the important, but now neglected right of modern citizens around the world – the right to the city. For the first time this topic was considered by the French sociologist H. Lefebvre. D. Garvey continues this work on the results of the 2008 economic crisis. The authors consider modern economic (financial crises, growth of real estate markets, impoverishment, exploitation, debt accumulation, fraud practices, etc.), social (urbanization, suburbanization, growing social inequality, polarization, segregation), geographical (spatial indicators of urbanization, import of the specified models of spatial arrangement of cities all over the world), moral (indifference, enmity, meanness in relations between well-off and low-paid citizens, disappearance of various forms of solidary collective urban activity). Problems of urban life are based on a critique of the complex processes of growth of capitalist management with parallel urbanization and globalization processes. The idea of finding a balance between the contradictory in social and private interests of urban activity is defended. The city acts as a set of tangible and intangible assets. Each type of society forms a special type of city. Each city can be "read" if you know the language of symbols. The influences of ideology and symbolism in the city on the consciousness of citizens are more than important. The modern existence of the city is characterized by the growing importance of the influences of the ideology of the ruling groups. The importance of active development of urban space is associated with material, historical, cultural, features of social life. The importance of creating and improving the city by residents is emphasized. The city is the result of creating space for a social life. Possible means of fighting for the right to the city through active public activity, formation of systemic coordinated protest movements in the world, creation of science about the city with the use of scientific analysis of urban problems, approaches to urban planning, use of modern technology, knowledge and art, are analyzed.